Safe and rapid radial hemostasis achieved using a novel topical hemostatic patch: Results of a first‐in‐human pilot study using hydrophobically modified polysaccharide‐chitosan. Issue 3 (12th February 2021) - Anchan, Rajeev; Venturini, Joseph; Larsen, Paul; Lee, Linda; Fernandez, Christopher; Besser, Stephanie A.; Kalathiya, Rohan; Paul, Jonathan; Blair, John; Nathan, Sandeep
Abstract: Background: The transradial approach (TRA) for catheter interventions decreases vascular complications and bleeding versus transfemoral approach. Reducing time to hemostasis and preventing radial artery occlusion (RAO) following TRA are important and incompletely realized aspirations. Objectives: This first‐in‐human study sought to evaluate the efficacy of a novel, topically applied compound (hydrophobically modified polysaccharide‐chitosan, hm‐P) plus minimal required pneumatic compression, to achieve rapid radial arterial hemostasis in post‐TRA procedures compared with de facto standards. Materials and Methods: About 50 adult patients undergoing 6 French diagnostic TRA procedures were prospectively enrolled. At procedure completion, a topical hm‐P impregnated patch was placed over the dermotomy and TR Band (TRB) compression was applied to the access site. This patch was used as part of a novel rapid deflation protocol with a primary outcome of time to hemostasis. Photographic and vascular ultrasound evaluation of the radial artery was performed to evaluate the procedural site. Results: Time to hemostasis was 40.5 min (IQR: 38–50 min) with the majority of patients ( n = 39, 78%) not requiring reinflation. Patients with bleeding requiring TRB reinflation were more likely to have low body weight and liver dysfunction, with absence of hypertension and LV dysfunction. The rate of RAO was 0% with predischarge radial artery patency documented in all patients using vascular ultrasound. One superficial hematoma was noted. No late bleeding events or cutaneous reactions were reported in the study follow‐up. Conclusions: Topical application of hm‐P in conjunction with pneumatic compression was safe and resulted in rapid and predictable hemostasis at the arterial puncture site.